The association between neurodevelopmental and behavioral problems and tobacco smoke exposure among 3-17 years old children - Yu Gao; Tong Wang; Zhizhen Duan; Yuepu Pu; Juan Zhang (Frontiers Media S.A., 2022)
Children being exposed to tobacco smoke can lead to poor developmental and behavioral problems. We aimed to explore the correlation between neurodevelopmental and behavioral problems (NBPs) and tobacco smoke exposure (TSE) among children aged 3-17 years. In this study, data were obtained from the 2018-2019 U.S. National Survey of Children's Health (NSCH). Children in the range of 3-17 years old were taken as the research subjects, and their parents were surveyed through questionnaires. TSE status was defined as one of three groups: no tobacco smoke exposure (no TSE), someone smoking but not inside the house (no home TSE), and someone smoking inside the house (home TSE). NBPs mainly included behavioral or conduct problems, intellectual disability, learning disability, speech or other language disorders, and developmental delay. We used the sampling weights provided by the NSCH to weight the data in order to obtain an unbiased population estimate. One-way ANOVA and Chi-square tests were performed to examine the difference of each variable. Logistic regression analysis and stratified analysis were carried out to investigate the association between NBPs and TSE. A total of 48,783 children were included in this study, with an average age of 10.1 years. In total 17.9% of all the participants were preschool children, 35.1% were school-age children, and 47.0% were school-age adolescents. More than 85.0% of children lived with no TSE. Over 90.0% of children were healthy in each NBP. Children living with home TSE and no home TSE showed significant adjusted odds ratios (aORs) compared with no TSE in four NBPs besides intellectual disability. The stratified analysis found aORs were higher for NBPs in preschool children compared to the school-age children and school-age adolescents. Male children living with home TSE showed higher aORs in moderate/severe NBP conditions. Our study indicated it is necessary to protect the health of young children from TSE by intervention measures.